Length–weight and length–length relationships for nine fish species from Lhasa River Basin, Tibet, China. (23rd April 2015) - Fan, L.‐Q.; Zhang, X.‐J.; Pan, G.
Summary The present study reports length–weight relationships (LWR) and length–length relationships (LLR) for five native freshwater fish species (Schizopygopsis younghusbandi, Triplophysa orientalis, T. tibetana, T. stewartii and T. stenura) and four introduced freshwater fish species (Pseudorasbora parva, Carassius auratus, Micropercops cinctus and Oryzias latipes) captured in the Lhasa River Basin, Tibet, China. Five of the LWRs are presented for the first time.